Perception of nursing students about behaviors and ethical aspects involved in patient data collection - Juliana Dias Reis Pessalacia; Bruna Martins Tavares; Fabiana Castro de Faria; Samantha Oliveira; Cristiane Chaves de Souza (Universidad de Antioquia, 2013)
Objective. To identify the perception of nursing students in relation to the behaviors and ethical issues involved in data collection from patients. Methodology. Descriptive and exploratory study with a qualitative approach, using the content analysis proposed by Bardin as the theoretical framework. Participants were students in the 7th period of the nursing undergraduate course at a public university located in the state of Minas Gerais, Brazil, in 2011. Data were collected through interviews. Results. From the analysis of the results, the following categories emerged: preservation of patients' intimacy and privacy, respect for patients' autonomy, experiences and feelings of students and training strategies relating to the nursing process during the undergraduate course. Conclusion. The nursing students are concerned with the ethical approach during data collection from patients and the preservation of their rights. Pedagogical practices should be reinforced that take into consideration the technical aspects, as well as those related to behaviors and ethics.